Contribution of brain network connectivity in predicting effects of polygenic risk and childhood trauma on state-trait anxiety. (August 2022) - Tian, Tian; Zhang, Guiling; Wang, Jian; Liu, Dong; Wan, Changhua; Fang, Jicheng; Wu, Di; Zhou, Yiran; Qin, Yuanyuan; Zhu, Hongquan; Li, Yuanhao; Li, Jia; et al.
Abstract: Background: Anxiety is usually attributed to adverse environmental factors, but it is known as a polygenic inheritance disease. Gene-environment interactions on the occurrence and severity of anxiety are still unclear. The role of brain network connectivity in the gene-environment effects on anxiety has not been explored and may be key to understanding neuropathogenesis and guiding treatment. Methods: This study recruited 177 young adults from the community that completed functional magnetic resonance imaging, Childhood Trauma Questionnaire (CTQ), state-trait anxiety scores, and whole exome sequencing. We calculated polygenic risk score (PRS) for anxiety and the sum score of CTQ, which are genetic and environmental factors that may affect anxiety, respectively. Abnormal brain network connectivity determined by the gene-environment effects and its associations with anxiety scores were then explored. Results: Except for the main effect of PRS or CTQ on intra-network connectivity, significant interactions were found in intra-network connectivity of visual network, default mode network, self-reference network, and sensorimotor network. Moreover, altered network connectivity was related to anxious tendency. In particular, the effect of CTQ on trait anxiety was mediated by the disrupted sensorimotor network, accompanied by a significant direct effect. However, the PRS influence on anxiety was mainly mediated through sensorimotor network paths, which exceeded the direct influence and was moderated by childhood trauma levels. Conclusions: These network-specific functional changes related to individual gene-environment risks advance our understanding of psychiatric pathogenesis of anxiety and provide new insights for clinical intervention. Graphical abstract: Image 1 Highlights: Altered brain networks determined by PRS and CTQ were related to anxiety. Disrupted sensorimotor network mediated the effect of CTQ on anxiety. The effects of PRS on anxiety through sensorimotor network were moderated by CTQ.